ANALISIS PENGGUNAAN QRIS DALAM MENINGKATKAN MINAT SEBAGAI MEDIA TRANSAKSI USAHA MIKRO DI NAGARI KOTO RANTANG, KEC.PALUPUAH, KAB.AGAM - Sarmitha Sarmitha; Amsah Hendri Doni (CV. ADIBA AISHA AMIRA, 2024)
This research is motivated by MSMEs that are not yet able to implement their capabilities, they will have difficulty competing in selling prices. Not only that, because some MSMEs do not use digital technology, business sales have not used much digital technology, online sales, as a result it is starting to feel difficult to compete with factories that have used technology for their operational and business sales. With the development of technology today, it is hoped that it can help micro business actors, one of which is in using QRIS as a business tool because QRIS allows for faster, easier and more economical business. With QRIS, micro business actors can accept electronic payments from various sources, including digital wallets, and payment applications that can expand the reach of their potential clients. This can contribute to increased marketing and the development of micro businesses. The purpose of this research is to identify the attention of micro business actors using QRIS as a business tool in Koto Rantang Village. Palupuh District, Agam Regency. and to identify the aspects of advocates and barriers to the attention of micro business actors regarding the use of QRIS as a business tool in Koto Rantang Village, Palupuh District. Palupuh, Agam Regency. This type of research is a qualitative field research. Next, the information collection method used is direct question and answer and selection. After that, the method of processing information and analyzing information is tried through 3 levels, namely information collection, information reduction, information presentation and the final step is drawing conclusions. In this research, the number of informants interviewed was 20 people who were focused on micro-business actors in Koto Rantang Village. The results of this research prove that initially, the lack of descriptions of residents in Koto Rantang Village, Palupuh District, Agam Regency regarding the use of QRIS as a business tool was due to limited technological insight. Usually, residents are still using cash or commonly called cash businesses in carrying out micro-businesses in the Village. Second, the lack of descriptions of residents in Koto Rantang Village, Palupuh District, Agam Regency regarding the use of QRIS as a business tool was due to limited technological insight. Usually, residents are still using cash or commonly called cash businesses in carrying out micro-businesses in the Village.